A Preliminary Result on Electrical Capacitance Tomography for Gas-solid Flow in Pneumatic Conveyor System - Nur Arina Hazwani Samsun Zaini; Ruzairi Abdul Rahim; Herman Wahid; Juliza Jamaludin; Mimi Faisyalini Ramli; Nasarudin Ahmad; Mohamad Shukri Abdul Manaf; Yusri Md. Yunos; Anita Ahmad; Ahmad Azahari Hamzah; Chan Kok San; Farah Aina Jamal Mohamad; et al. (Penerbit UTM Press, 2024)
Indexed by MyCite